Grain legumes evolution and genetic resources - Smartt, J. (Cambridge University Press, 1990)
This volume provides a wide-ranging survey of all the major grain legumes from the standpoint of both their evolution and their potential for further development and improvement as economically important food crops. The legumes have a vital role to play in both the developed and developing worlds by providing an alternative nitrogen source to the artificial fertilizers, which, although boosting cereal yields, often have had adverse environmental effects. The grain legumes are a valuable crop possessing the ability to fix nitrogen by Rhizobium biosynthesis and thus contribute to the natural nitrogen cycle. The book surveys the changes which have occurred in the course of domestication of the plants which have evolved into our pulse crops and oilseed legume crops. The author then discusses the benefits to be gained from evaluation and improvement of grain legume genetic resources. It is through this comparative approach that the overall potential of these crops is highlighted